A Semiotic Analysis of Icons, Indexes, and Symbols in the Kutai Folktale Puan and Si Taddung and Their Cultural Meanings - Cesarida, Arneta; Ahmad, Muhammad Rusydi; Arifin, Syaiful; Nurdin, Nurdin; Setyawati, Meita (The Future of Education Journal, 2025)
This study analyzes the forms of icons, indexes, and symbols as well as the cultural meanings embedded in the Kutai folktale Puan and Si Taddung by applying Charles Sanders Peirce’s semiotic framework. The study is grounded in the issue of diminishing local cultural literacy and the need to strengthen cultural identity through literature-based learning. Using a qualitative descriptive design, data were collected through documentation and close reading of narrative excerpts containing visual, situational, and symbolic signs. The data were categorized based on Peirce’s triadic model representamen, object, and interpretant and interpreted according to the cultural context of the Kutai community. The findings reveal that icons appear in depictions of the village landscape, characters, and cultural objects; indexes emerge through causal signs linked to events such as danger, illness, and moral obligation; and symbols represent deeper cultural values, including filial piety, bravery, honor, and spiritual purity. These signs collectively articulate the core principles of Kutai culture Politeness , identity and reputation, and honor and dignity. The study concludes that the folktale functions not only as a narrative of entertainment but also as a medium of cultural transmission and character education, highlighting its relevance for strengthening local wisdom within contemporary educational practice.